IMPLEMENTASI KEBIJAKAN PENDIDIKAN LINGKUNGAN HIDUP SMP NEGERI 1 BAGAN SINEMBAH MENUJU SEKOLAH ADIWIYATA MANDIRI - Kiki Ardian; Makhdalena Makhdalena; Zulkifili N (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2018)
Environmental education is one of important policy that isssued by the governmentas the effort of delivering education at whole schools by Adiwiyata programme. This researchwas aimed to obtain the description of the implementation environtmental education policy ofSMP Negeri 1 Bagan Sinembah. The approach of the research used qualitative descriptive.Data collection was done by the researchers themselves as a key instrument, whereas todetermine the source of human data using snowball sampling technique. Data was collectedby means of; (1) in-depth interviews; (2) The participant observation; and (3) study thedocumentation. For data analysis using descriptive techniques whose application is done inthree flow of activities, namely data reduction, data presentation, and conclusion or verification.The result showed that, first, the understanding of school people about the concept, goal andprinciple of Adiwiyata Mandiri was good. Second, the commitment of school people about theenvironment education policy was quite good eventhough some school people showed nospirit and unready attitude to run the Adiwiyata programme. Third, The programmes of AdiwiyataMandiri were socializaiton to the candidate of next adiwiyata school, environmental educationand Clean Saturday programme. The programmes runs quite well. Fourth, the implementorand financial source in implementing the environmental education policy at SMP Negeri 1Bagan Sinembah was not adequate. The results can be taken into consideration for otherschools in making their schools as Adiwiyata mandiri.